Dimensi Keadilan Pada Penetapan Ahli Waris - Hajar M (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
Allah the Almighty is convinced as the judge and law maker who are the Most Just. Every law, includes inheritance law is created by Him very justly. To determine the values of justice, it is necessary to do a research and deep observation. This article explores justice dimension of inheritance law, especially to heir. Justice dimension on determining heirs involves three things, namely descent, priority level, and inheritance obstacle. The descent on heir is started from birth which causes blood relationship that responsibilities between inheritance owner and heir appear. It also includes rights and duties on marriage relationship. Priority level among heirs is based on responsibility intensity so the justice on rights of heirs which fits status and relatives power to inheritance owner appears. To give the other heirs chances receiving equal rights, there are some rights of heirs are reduced. Inheritance obstacle owns justice values because of no responsibilities among of them. Thus, mutual commitment for implementing Islamic law of inheritance is needed.